From "trust" to "trustworthiness": Retheorizing dynamics of trust, distrust, and water security in North America. (March 2023) - Wilson, Nicole J; Montoya, Teresa; Lambrinidou, Yanna; Harris, Leila M; Pauli, Benjamin J; McGregor, Deborah; Patrick, Robert J; Gonzalez, Silvia; Pierce, Gregory; Wutich, Amber
Assumptions of trust in water systems are widespread in higher-income countries, often linked to expectations of "modern water." The current literature on water and trust also tends to reinforce a technoscientific approach, emphasizing the importance of aligning water user perceptions with expert assessments. Although such approaches can be useful to document instances of distrust, they often fail to explain why patterns differ over time, and across contexts and populations. Addressing these shortcomings, we offer a relational approach focused on the trustworthiness of hydro-social systems to contextualize water-trust dynamics in relation to broader practices and contexts. In doing so, we investigate three high-profile water crises in North America where examples of distrust are prevalent: Flint, Michigan; Kashechewan First Nation; and the Navajo Nation. Through our theoretical and empirical examination, we offer insights on these dynamics and find that distrust may at times be a warranted and understandable response to experiences of water insecurity and injustice. We examine the interconnected experiences of marginality and inequity, ontological and epistemological injustice, unequal governance and politics, and histories of water insecurity and harm as potential contributors to untrustworthiness in hydro-social systems. We close with recommendations for future directions to better understand water-trust dynamics and address water insecurity.